Using a word «mood» in compositions of Turmaganbet (Eurasian Journal of Philology Science and Education, 2015)
In this article, there is analyzed a part of Turmaganbet’s creation for science, whom researched skills of Kazakh literary science’s laboratory. And there is says about his skills and mastery, about compositions which learns akyn’s ambition. At the same time, discussed using of a word «mood» in poetry of akyn’s inner world. Explained meaning of words «faith», «morality».
Keywords: рoet; mirovozrenie; psychology; spirituality; science